Goose astrovirus induces apoptosis and endoplasmic reticulum stress in gosling hepatocytes - Zhihua Lu; Haiqin Li; Xiaona Gao; Duanfeng Fu; Haoyu Huang; Cheng Huang; Meiqin Wu; Xiaoquan Guo (Poultry Science)
The ongoing Goose astrovirus (GoAstV) epidemic, which primarily infects goslings causing severe liver damage, has inflicted considerable damage on the poultry industry. Endoplasmic reticulum stress (ERS) is a significant modulator of several viral infections, while severe ERS may result in apoptosis. This study examined the roles and possible mechanisms of ERS and apoptosis in GoAstV-induced liver injury in goslings. Two hundred Xingguo gray geese were chosen and randomly separated into two groups (Con and Dis). The Dis group received a subcutaneous injection of GoAstV genotype 2 (GoAstV-2) JX01 (2 × 106 TCID50/0.2 mL), whereas the Con group received a subcutaneous injection of 0.2 mL physiological saline, both at 1 day of life. Subsequent analyses demonstrate that the levels of aspartate aminotransferase (AST) and alanine aminotransferase (ALT) increased following GoAstV infection. Hematoxylin and eosin (HE) staining revealed swollen and ruptured hepatocytes, with significant inflammatory cell infiltration. Electron microscopy revealed expansion of the endoplasmic reticulum (ER) and aggregation of chromatin at the periphery. TUNEL testing further demonstrated an increase in the quantity of positive cells. RT-qPCR and Western blot analyses indicated that GoAstV infection enhanced the expression of ER Ca2+ release channels (IP3R and RYR) and calmodulin-dependent protein kinase II (CaMKII), while decreasing the expression of ER Ca2+ uptake channels (SERCA). Further, GoAstV infection activated ERS-related factors, including GRP78, IRE1α, PERK, ATF6, eIF2α, ATF4, CHOP, TRAF2, and JNK, induced the expression of pro-apoptotic factors (Caspase-3, Caspase-9, and Bax), and inhibited the mRNA and protein expression of the anti-apoptotic factor Bcl-2. Correlation analysis further revealed a potential relationship among ERS gene expression, apoptotic gene expression, and liver injury. In summary, GoAstV infection can lead to liver injury by interfering with ER Ca2+ homeostasis, exacerbating ERS and inducing hepatocyte apoptosis.